Impacts of water-sediment regulation on spatial-temporal variations of heavy metals in riparian sediments along the middle and lower reaches of the Yellow River - Qinghe Zhao (Elsevier, 2021)
The water-sediment regulation scheme (WSRS) of dams influences the desorption, resuspension, and deposition processes of riparian sediments, which in turn affect the spatial-temporal variations of heavy metals (HMs) in riparian sediments and leads to severe degradation of soil and water quality. However, the difference between the trapping effect of dams and the redistribution effects of the WSRS on HMs in riparian sediments, as well as the consecutively seasonal change of HMs after the WSRS, are rarely reported. To fill this gap, the concentrations of six HMs including Cd, Cr, Cu, Ni, Pb, and Zn in riparian sediments along the Xiaolangdi Dam (XLD) Reservoir and its downstream reach were investigated, and the contamination level and potential ecological risk of HMs were assessed, to differentiate the effects of the XLD and its WSRS on the concentration, contamination level, and potential ecological risks of HMs. The results indicated that the mean HM concentrations in riparian sediments were higher than the background values in the study area and showed significant spatial and temporal variations. However, the regional differences of HM concentrations caused by the trapping effect of the XLD were less than the seasonal differences caused by the redistribution effects of the WSRS. The contamination and ecological risk assessment indicated that riparian sediments in the study area were contaminated by the six HMs, particularly by Cd and Pb, which overall exhibited a high and moderate ecological risk, respectively. The sources for Pb were likely agricultural inputs, while the sources for Cd should be attributed to both industrial and agricultural inputs. Overall, the trapping effect of the XLD led to the accumulation of HMs in riparian sediments along the reservoir area, while the regulation effects of the WSRS resulted in the redistribution of HMs in riparian sediments from the reservoir area to the downstream reach.